Diversidad de anfibios en bosques sobre arena blanca y arcilla de la estación biológica José Álvarez Alonso, Loreto, Perú - Rojas Padilla, Omar (2017)
The present study was conducted in July 2016 with the objective of evaluating the diversity of amphibians present in the forests on white sand and clay of the biological station "José Álvarez Alonso" in the National Reserve "Allpahuayo Mishana". Thirty transects of 100 meters in length were established in each type of forest mentioned (3 km of transects in each forest), which were evaluated systematically for one hour each (3 transects per night). In the withe sand forests, 103 individuals belonging to 22 species grouped in 06 taxonomic families were recorded; while, in the clay forests, 167 individuals of 42 species grouped in 09 taxonomic families were recorded. In total, 270 individuals of 48 species belonging to 09 amphibian families have been recorded. We consider Tepuihyla tuberculosa, Phyllomedusa bicolor, Pristimantis padiali, Ranitomeya reticulata, as some of the potential species for tourist activities and of conservation interest. It is concluded that the "José Álvarez Alonso" Biological Station contains a high diversity of species; that the forests on clay have more amphibian diversity than the sandy ones; and that there are species of interest that can be included in future conservation and scientific research plans.